A new dermocosmetic containing retinaldehyde, delta-tocopherol glucoside and glycylglycine oleamide for managing naturally aged skin: results from in vitro to clinical studies - Rouvrais C; Bacqueville D; Bogdanowicz P; Haure M; Duprat L; Coutanceau C; Castex-Rizzi N; Duplan H; Mengeaud V; Bessou-Touya S (Dove Medical Press, 2017)
Céline Rouvrais,1,* Daniel Bacqueville,2,* Patrick Bogdanowicz,2,* Marie-José Haure,2 Laure Duprat,2 Christine Coutanceau,3 Nathalie Castex-Rizzi,2 Hélène Duplan,2 Valérie Mengeaud,1 Sandrine Bessou-Touya2 1Clinical Skin Research Center, 2Department of Pharmacology, Pierre Fabre Dermo-Cosmétique, Toulouse, 3Laboratoire Dermatologique Avène, Lavaur, France *These authors contributed equally to this work Introduction: Natural aging of skin tissues, the addition of the cumulative action of the time and radiation exposure result in skin atrophy, wrinkles and degeneration of the extracellular matrix (ECM). The aim of the study was to investigate the beneficial effect of a combination containing retinaldehyde (RAL), delta-tocopherol glucoside (delta-TC) and glycylglycine oleamide (GGO) and of a dermocosmetic containing the combination. Materials and methods: The protective effect of the combination was assessed through in vitro gene expression of ultraviolet (UV)-irradiated fibroblasts. A skin aging assay using UV light on ex vivo skin samples and a clinical study conducted in 36 women aged from 35 to 55 years with a minimum of level 4 to a maximum of level 6 on the crow’s feet photoscale assessed the antiaging effect of the dermocosmetic. Results: When added to UV-irradiated fibroblasts, the combination substantially improved the ECM in activating the elastin fiber production (fibrillin 2, fibulin 1 and 5 and lysyl oxidase-like 2) as well as that of proteins involved in the cellular ECM interactions (integrin β1, paxillin and actin a2). An ex vivo photodamaged human skin model showed that the dermocosmetic formulation containing the combination of the active ingredients protected the elastic network against UV-induced alterations including both elastin and fibrillin-rich fibers in the dermis. A daily application of the dermocosmetic for 2 months on naturally aged skin resulted in a statistically significant improvement (p<0.05) of visible signs of aging comprising crow’s feet, wrinkles and periocular fine lines. Finally, the formulation was well tolerated. Conclusion: The dermocosmetic containing RAL, delta-TC and GGO provides a substantial benefit in the daily care of naturally aged skin in women aged 35–55 years. Keywords: glycylglycine oleamide, delta-tocopherol glucoside, retinaldehyde, preclinical aged skin model, statistics, formulation